Cytokine release syndrome in COVID-19: Innate immune, vascular, and platelet pathogenic factors differ in severity of disease and sex. Issue 1 (15th September 2020) - Petrey, Aaron C; Qeadan, Fares; Middleton, Elizabeth A; Pinchuk, Irina V; Campbell, Robert A; Beswick, Ellen J
Abstract: COVID-19 rapidly emerged as a crippling public health crisis in the last few months, which has presented a series health risk. Understanding of the immune response and biomarker analysis is needed to progress toward understanding disease pathology and developing improved treatment options. The goal of this study is to identify pathogenic factors that are linked to disease severity and patient characteristics. Patients with COVID-19 who were hospitalized from March 17 to June 5, 2020 were analyzed for clinical features of disease and soluble plasma cytokines in association with disease severity and sex. Data from COVID-19 patients with acute illness were examined along with an age- and gender-matched control cohort. We identified a group of 16 soluble factors that were found to be increased in COVID-19 patients compared to controls, whereas 2 factors were decreased. In addition to inflammatory cytokines, we found significant increases in factors known to mediate vasculitis and vascular remodeling (PDGF-AA, PDGF-AB-BB, soluble CD40L (sCD40L), FGF, and IP10). Four factors such as platelet-derived growth factors, fibroblast growth factor-2, and IFN-γ-inducible protein 10 were strongly associated with severe disease and ICU admission. Th2-related factors (IL-4 and IL-13) were increased with IL-4 and sCD40L present at increased levels in males compared with females. Our analysis revealed networking clusters of cytokines and growth factors, including previously unknown roles of vascular and stromal remodeling, activation of the innate immunity, as well activation of type 2 immune responses in the immunopathogenesis of COVID-19. These data highlight biomarker associations with disease severity and sex in COVID-19 patients. Graphical Abstract: Inflammatory cytokines and vasculitis factors are increased in COVID-19 infection with links to disease severity and sex variables.